Assessment of bladder filling during prostate cancer radiation therapy with ultrasound and cone-beam CT - Chauhan, Kiran; Ebner, Daniel K.; Tzou, Katherine; Ryan, Karen; May, Jackson; Kaleem, Tasmeem; Miller, Daniel; Stross, William; Malouff, Timothy Dean; Landy, Robin; Strong, Gerald; Herchko, Steve; et al. (Frontiers in Oncology, 2023)
Prostate cancer patients undergoing external beam radiation therapy (EBRT) benefit from a full bladder to decrease bowel and bladder toxicity. Ultrasound may offer a proxy metric for evaluation, sparing CBCT dosing. Patients were prospectively enrolled pre-simulation from January 2017 to February 2018. Bladder volume was evaluated prior to RT using US daily and CBCT for three daily treatments and then weekly unless otherwise indicated. 29 patients completed median 40 days of RT, resulting in 478 CBCT and 1,099 US bladder volumes. 21 patients were treated to intact glands and 8 to the post-prostatectomy bed. Median patient age was 70 years. Bladder volume on CBCT and US positively correlated (r = 0.85), with average bladder volume for all patients of 162 mL versus 149 mL, respectively. Bladder volume during treatment was consistently lower than the volume at CT simulation (153 mL vs 194 mL, p<0.01) and progressively declined during treatment. Patients older than 70 years presented with lower average bladder volumes than those < 70 years (122 mL vs 208 mL, respectively, p<0.01). Patients with the highest agreement between CBCT and US (<10% variability) had higher average bladder volumes (192 mL vs 120 mL, p=0.01). US was found to be an accurate measure of bladder volume and may be used to monitor daily bladder volumes in patients being treated with radiation for prostate cancer.